Evaluation of the effect of irrigants on the accuracy and repeatability of three electronic apex locators: an ex vivo study (Research, Society and Development, 2021)
Objective: To evaluate the effect of 2% chlorhexidine (CHX) and 2.5% sodium hypochlorite (NaOCl) on the accuracy and repeatability of three Electronic Apex Locators (EALs). Methodology: Thirty one human teeth were connected to a platform, irrigated with 2.0% CHX, and obtained two readings, again irrigated with 2.5% NaOCl and obtained two more readings. The distance between the tip of the file and the apical constriction was measured. Repeatability was calculated using the intraclass correlation coefficient (ICC) and repeatability coefficient (CR). Results: For CHX 2%, with the Mini Apex Locator, 25 of 31 electronic measurements were accurate (80.6%), 28 of 31 measurements for iPex (90.3%) and for Root ZX II 26 (83, 9%). For 2.5% NaOCl, with the Mini Apex Locator, 25 of the 31 measurements were accurate (80.6%), 28 of the 31 measurements for the iPex (90.3%) and for the Root ZX II, 24 (77, 4%). There were no differences between the two irrigants (p>0.05). The values ​​(ICC) were 0.975 and 0.994 for the Mini Apex Locator, 0.981 and 0.971 for the i Pex and 0.994 and 0.995 for the Root ZX II. When using CHX, the (CR) was 0.196 for the Mini Apex Locator, 0.152 for the iPex and 0.088 for the Root ZX II. When using 2.5% NaOCl, the (CR) was 0.088 for the Mini Apex Locator, 0.196 for the iPex and 0.088 for the Root ZX II. Conclusions: The use of 2% CHX and 2.5% NaOCl did not affect the accuracy and repeatability of the three devices.